Technology's role in Mapudungun language teaching and revitalization. (September 2019) - Quintrileo Llancao, Elizabeth Jacqueline
The Mapudungun language spoken by the Mapuche people in southern Chile is one of the thousands of severely endangered languages in the world today. Despite efforts by the Mapuche people to support it, the language remains threatened. The study reported here is part of an effort to more effectively support the revitalization of Mapudungun aimed at developing a community- and technology-based model for the teaching of the language. The study was divided into two stages: first, the design and development of the model; second, the evaluation of the model based on quasi-experimental research with a pre-test and a post-test. Then, the participants were surveyed to obtain information regarding their beliefs toward the use of technology in the teaching–learning process of Mapudungun. The study's results indicate that technology can facilitate Mapuche language learning and revitalization.